Integration interaction of managing subjects road transport, forms and determination of effect - V. L. Eichler; A. A. Demidenko (Вестник СибАДИ, 2017)
The article investigates the evaluation of integration interaction of managing subjects of road transport, taking into account the theory of self-organization. The article explains that the integration on the one hand, acts as an objective process, and on the other hand is the result of conscious management decisions leaders trucking companies when defining the role of motivational factors. The motives are expressed in terms of integration activities of organizations of self-organization, by means of which road transport companies have the ability to reduce the potential of basic and overhead costs.